Implementasi Ragam Hias Nusantara dalam Perancangan Desain Karakter Game Nuswantara - Hadida, Yasmin Wita Al; Wibawa, Mahendra (Jurnal Desain Komunikasi Visual Asia, 2024)
Archipelago decoration is a pattern of beauty that is repeated in works of art influenced by Indonesian culture. Indonesian decorations are reflected in traditional games and have the opportunity to be introduced into modern games. This design aims to create characters with Indonesian decorative patterns that are attractive and can be implemented into Nuswantara games. The design method used in this design is Design Thinking. The data collected comes from project briefs, literature studies, and observations. This design resulted in 6 character sheets and concept art representing the Kutai kingdom, Sriwijaya kingdom, Ancient Mataram kingdom, Singasari kingdom, Majapahit kingdom and Kalinga kingdom. This design also produces supporting media in the form of art books, loading screens and merchandise. After that, a trial phase was carried out with 3 validators, namely the Nuswantara IP holder as the main resource person, the Let's Play project manager, and a professional illustrator. The test results of the designed media show that the design looks attractive and is considered to have met the character design needs of the Nuswantara game well.